2005
DOI: 10.1089/ees.2005.22.891
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in Houston Ship Channel Tissue and Sediment

Abstract: Concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) were measured in sediment, catfish, and crab tissue from 45 locations in the Houston Ship Channel in Texas in the Summer of 2002. Concentrations of individual 2378-substituted congeners ranged from 0. 1 to 42,000 ng/kg dry wt, from 0. 1 to 230 ng/kg wet wt, and from 0.1 to 260 ng/kg wet wt fo r sediment, catfish, and crab samples, respectively. OCDD concentrations in sediments were up to two orders of magnitude higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…A similar proportion (85%) was found for OCDD in 2378 substituted PCDD/Fs in the Houston Ship Channel (Suarez et al 2005). The second most common congener in the present study is 1234678 HpCDD (between 8.4% and 11.5%).…”
Section: Congener Profiles In Sedimentssupporting
confidence: 84%
See 2 more Smart Citations
“…A similar proportion (85%) was found for OCDD in 2378 substituted PCDD/Fs in the Houston Ship Channel (Suarez et al 2005). The second most common congener in the present study is 1234678 HpCDD (between 8.4% and 11.5%).…”
Section: Congener Profiles In Sedimentssupporting
confidence: 84%
“…Yunker et al (2002) concluded that PCDFs from chlorine bleaching in British Columbia accumulated more readily from sediments to Dungeness crab than did PCDDs. Compared with sediments, a greater abundance of PCDFs than PCDDs, especially the octaforms, was also observed in crab (Callinectes sapidus) in Houston Ship Channel (Suarez et al 2005). The objective of our study is to help remedy the incomplete knowledge of these relationships between PCDD/Fs and DL-PCBs in sediments and crabs by evaluating the connections between the quantity, toxicity, and compositional profile of PCDD/Fs and DL-PCBs in the blue crab (C. sapidus) and sediments in three anthropogenically altered estuaries.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since detection levels for PCDD/Fs are relatively low (0.0024-1.4961 pg L À1 for dissolved and 0.0038-5.0388 pg L À1 for suspended), samples were collected using a high-volume technique at volumes ranging from 250 L to 500 L to allow for detection of PCDD/Fs, when present, at concentrations above their detection limits. More details regarding sample collection and chemical analysis methods can be found in Suarez et al (2005Suarez et al ( , 2006a and in the SI. PCDD/Fs were quantified by high-resolution gas chromatography/high-resolution mass spectrometry (HRGC/HRMS) using EPA Method 1613B at a commercial laboratory.…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The paper quantifies the concentrations of the 17 most toxic PCDD/F congeners, or 2,3,7,8-substituted PCDD/F congeners (USEPA, 1994) in effluent discharges from the Houston Metropolitan area into the Houston Ship Channel (HSC), a water body that exhibits elevated levels of PCDD/Fs in its sediment, water, and tissue (Suarez et al, 2005;Suarez et al, 2006a;Suarez et al, 2006b;Yeager et al, 2007;Howell et al, 2008;Dean et al, 2009;Lakshmanan et al, 2010;Howell et al, 2011;Rifai et al, 2013). The purpose of the study was to identify patterns or differences in PCDD/F congener and homolog distribution among different treatment plant types and within the dissolved and suspended phases.…”
Section: Introductionmentioning
confidence: 99%